PERTANGGUNGJAWABAN PIDANA TERHADAP PENGEMUDI OJEK ONLINE SEBAGAI PERANTARA DALAM PEREDARAN NARKOTIKA DI INDONESIA - Ambeua, Yandi; Elisabeth Wangga, Maria Silvya (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Narcotics circulation has used a new modus operandi, namely utilizing online motorcycle taxi drivers as intermediaries for buying and selling narcotics to facilitate delivery and not be suspected by law enforcement officers so that the perpetrators avoid legal proceedings, the driver has a role in narcotics circulation so that the responsibility and punishment are attached to him. This study uses a normative juridical research type that is descriptive analysis, using secondary data obtained from library materials, primary, secondary and tertiary legal materials obtained and regulations, decisions and legal dictionaries, where the data is processed qualitatively by drawing conclusions deductively. Conclusion 1) In this case there is no mens rea or malicious intent of the defendant, in the absence of mens rea, the online motorcycle taxi driver cannot be held fully criminally responsible, mens rea is the main element to determine whether a person can be held accountable and there is no intention to violate the law. 2) Article 114 of the Narcotics Law does not require an element of intent so that there is no legal justice. In order to create a sense of justice, it is necessary to add an element of intent to the formulation of Article 114 of the Narcotics Law because this article does not require an element of intent.Keywords: Drug Distribution, Intermediary, Online Motorcycle Taxi Driver.